Analysis of reported e-prescribing near misses in King Saud Medical City, Riyadh - Al-Zaagi IA; Aldhwaihi KA; Al-Dossari DS; Salem SO; Qureshi NA (Dove Medical Press, 2013)
Ibrahim Abdulaziz Al-Zaagi,1 Khalid Abdulrahman Aldhwaihi,2 Dalal Salem Al-Dossari,1 Sara Osama Salem,3 Naseem Akhtar Qureshi41Pharmaceutical Care and Medication Safety, King Saud Medical City, 2General Administration of Pharmaceutical Care, Ministry of Health, 3Drug Poisoning Information Center, King Saud Medical City, 4General Administration of Research and Studies, Ministry of Health, Riyadh, Kingdom of Saudi ArabiaBackground: In the health care context, a “near miss” is a drug presciption error that happened but did not affect the patient. These errors are captured and corrected before reaching the patient fortuitously or purposefully by designed system controls. This study analyzed the reported near misses in a tertiary care hospital in Riyadh city.Methods: This cross-sectional study evaluated consecutively collected near miss report forms over a period of 6 months from January 1, 2012 to June 30, 2012.Results: The total number of near miss report forms was 1,025 and each form contained one or more near misses. Of these near miss report forms, 58.73% (n = 602) were related to male patients. Most frequently reported near misses were wrong frequency (n = 266, 25.95%), followed by improper doses (n = 250, 24.39%), wrong drug prescribed (n = 126, 12.29%), wrong duration (n = 97, 9.46%), wrong concentration (n = 92, 8.98%), and wrong dosage form (n = 57, 5.56%). Stages where most near misses were identified included transcription and entering (n = 676, 55.32%), physician ordering (n = 397, 32.49%), and dispensing and delivery (n = 115, 9.41%). Physicians and nurses made most of the near misses (n = 929, 89.1%), whereas pharmacists identified most of the near misses (n = 1,002, 97.3%). Most frequently reported reasons for near misses were lack of staff training (n = 419, 34.12%), communication problems related to drug order (n = 387, 31.5%), staff, workflow and milieu problems (n = 199, 16.2%), and missing drug information (n = 121, 9.85%). Sites related to most near misses were the general hospital outpatient department (n = 453, 44.67%), the general hospital emergency room (n = 237, 23.37%), and the maternity hospital outpatient department (n = 203, 20.02%). Pharmacists intervened by correcting drug-related items in most near misses (n = 702, 34.58%), waited for a response from source of errors (n = 358, 17.64%), called reporter for clarifications (n = 471, 23.20%), or did not dispense the drug (n = 331, 16.3%). Drugs most frequently involved in near misses were anti-infective (n = 239, 22.61%), cardiovascular (n = 207, 19.58%), and central nervous system (n = 154, 14.57%) agents.Conclusion: This prospective study provides some important tentative pharmacovigilance insights into near misses, which are comparable with current international trends in near misses. Further studies on near misses are warranted in the Kingdom of Saudi Arabia.Keywords: near miss, medication errors, e-prescribing, electronic prescribing system, Saudi Arabia